2021
DOI: 10.1093/gji/ggab182
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of electromagnetic induction data using a novel wavelet-based and scale-dependent regularization term

Abstract: Summary The inversion of electromagnetic induction data to a conductivity profile is an ill-posed problem. Regularization improves the stability of the inversion and a smoothing constraint is typically used. However, the conductivity profiles are not always expected to be smooth. Here, we develop a new inversion scheme in which we transform the model to the wavelet space and impose a sparsity constraint. This sparsity constrained inversion scheme will minimize an objective function with a least-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In this section, we extend the work of Deleersnyder et al (2021) into two dimensions. The 2D scaledependent wavelet-based regularization term will be described in a step-by-step manner.…”
Section: Scale-dependent Wavelet-based Complexity Measurementioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we extend the work of Deleersnyder et al (2021) into two dimensions. The 2D scaledependent wavelet-based regularization term will be described in a step-by-step manner.…”
Section: Scale-dependent Wavelet-based Complexity Measurementioning
confidence: 99%
“…This is the foundation of the sparsifying nature of the wavelet transform. A more detailed example is found in Deleersnyder et al (2021) or in standard works about wavelet theory, such as Mallat (1999).…”
Section: Measuring Model Complexity With the Discrete Wavelet Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the additional regularization parameters is not straightforward and often arbitrary, but may be estimated objectively from time-lapse data (Nguyen et al, 2016). With a similar goal, but a completely different approach, Deleersnyder et al (2021) present a regularization method, which transforms the model into the wavelet domain. This novel scale-dependent regularization term can favor both blocky and smooth models, as well as high-amplitude features embedded in an otherwise smooth model domain.…”
Section: Incorporation Of Geological Realismmentioning
confidence: 99%
“…Hansen et al [53] studied the effect of using approximate forward models on the inversion of GPR cross-hole travel time data and demonstrated that the modelling error could be more than one order of magnitude larger than the measurement error, leading to unwanted artifacts in the realizations from the posterior probability. For EM methods, studies have demonstrated the negative effect of using fast approximations of the forward model on the accuracy of the inversion [54][55][56]. In particular, for TDEM methods, using accurate models is computationally too expensive to be attractive for stochastic inversion of large data sets, as are those obtained from surveys with airborne or tTEM methods.…”
Section: Introductionmentioning
confidence: 99%